To devalue or not to devalue? How East European countries responded to the outflow of capital in 1997-99 and in 2008-09 - Vladimir Popov (Transformation, Integration and Globalization Economic Research (TIGER), 2011)
If there is a negative terms of trade or financial shock leading to the deterioration in the balance of payments, there are two basic options for a country that has limited foreign exchange reserves. First, a country can maintain a fixed exchange rate (or even a currency board) and wait until the reduction of foreign exchange reserves leads to the reduction of money supply: this will drive domestic prices down and stimulate exports, raise interest rates and stimulate the inflow of capital, and finally will correct the balance of payments. Second, the country can allow the devaluation of national currency - flexible exchange rate will automatically bring the balance of payments back into the equilibrium. Because national prices are less flexible than exchange rates, the first type of adjustment is associated with the greater reduction of output. The empirical evidence on East European countries and other transition economies for 1998-99 period (outflow of capital after the 1997 Asian and 1998 Russian currency crises and slowdown of output growth rates) suggests that the second type of policy response (devaluation) was associated with smaller loss of output than the first type (monetary contraction). 2008-09 developments provide additional evidence for this hypothesis.
Keywords: 330